2008
DOI: 10.1073/pnas.0709737104
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian acyl-CoA:lysophosphatidylcholine acyltransferase enzymes

Abstract: The mammalian RBC lacks de novo lipid synthesis but maintains its membrane composition by rapid turnover of acyl moieties at the sn-2 position of phospholipids. Plasma-derived fatty acids are esterified to acyl-CoA by acyl-CoA synthetases and transferred to lysophospholipids by acyl-CoA:lysophospholipid acyltransferases. We report the characterization of three lysophosphatidylcholine (lysoPC) acyltransferases (LPCATs), products of the AYTL1, -2, and -3 genes. These proteins are three members of a LPCAT family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 30 publications
1
107
1
Order By: Relevance
“…Despite recent progress on the molecular cloning of its biochemical components (Benghezal et al, 2007;Chen et al, 2007;Jain et al, 2007Jain et al, , 2009Tamaki et al, 2007;Hishikawa et al, 2008;Soupene et al, 2008;Ståhl et al, 2008;Zhao et al, 2008;Kazachkov et al, 2008), the metabolic significance of LPCAT in acyl lipid metabolism remains to be fully explored. LPCAT1 and LPCAT2 were the only two genes from Arabidopsis capable of complementing the yeast lca1D mutant in a functional screening (Zheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent progress on the molecular cloning of its biochemical components (Benghezal et al, 2007;Chen et al, 2007;Jain et al, 2007Jain et al, , 2009Tamaki et al, 2007;Hishikawa et al, 2008;Soupene et al, 2008;Ståhl et al, 2008;Zhao et al, 2008;Kazachkov et al, 2008), the metabolic significance of LPCAT in acyl lipid metabolism remains to be fully explored. LPCAT1 and LPCAT2 were the only two genes from Arabidopsis capable of complementing the yeast lca1D mutant in a functional screening (Zheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because the enzyme is expressed mainly in the brain, it was suggested that LPEAT2 is an important enzyme for the biogenesis of brain PE. In addition, it has been reported that AGPAT7 (LPEAT2) has LPCAT activity in red blood cells, although its activity is relatively weak (43).…”
Section: Acyltransferases In the Remodeling Pathway (Lands' Cycle)mentioning
confidence: 99%
“…As previously described ( 24 ), qualitative identification of individual PL molecular species was based on their calculated theoretical monoisotopic mass values and subsequent species utilized is 1-alkyl lysoPC and 1-alkenyl lysoPC, indicating the likely importance of this enzyme in platelet activating factor (PAF) synthesis. A third mouse paralog can also esterify lysoPC with a preference for palmitoyl-CoA ( 11 ).…”
Section: Electrospray Ionization-mass Spectrometry (Esi-ms)mentioning
confidence: 99%